Assessment of the combined effect of laser phase noise and intercore crosstalk on the outage probability of DD OOK Systems - Rebola, J. L.; Alves, T. M. F.; Cartaxo, A. V. T. (2019 21st International Conference on Transparent Optical Networks (ICTON), 2019)
We study the influence of the combined effect of laser phase noise and intercore crosstalk on the outage probability of direct-detection 10 Gbit/s on-off keying optical communication systems. We show that the laser phase noise can affect significantly the outage probability, for lasers with linewidths in the MHz range, for low and high skew-bit rate products. We also show that the laser phase noise effect on the received eye-pattern is qualitatively similar to the one found for high skew-bit rate product in the absence of laser phase noise.